Green Economy/Green Economy in the Perspective of the Qur'an - A. Hanief Zayyadi (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
Green economy is a development concept that integrates economic growth, social welfare, and environmental sustainability. In the Islamic perspective, this concept has a strong foundation reflected in the teachings of the Qur'an about balance (al-mizan), the prohibition of causing damage (fasad fil ardh), the wise use of resources (tasharruf bi al-hikmah), the mandate as a caliph on earth, and the principle of sharing for social welfare. The method used in this study is library research. Researchers refer to literature studies such as books and journals related to the issue taken, namely the green economy in the perspective of the Qur'an. The results of the study show that the concept of a green economy also supports global sustainability goals, as stated in the Sustainable Development Goals (SDGs), while also containing spiritual and ethical values ​​that are important for increasing public awareness. With a holistic approach that combines Islamic values, modern technology, and economic strategy, Indonesia has a great opportunity to lead the transition to equitable low-carbon development, while also being an example for the world in efforts to preserve the earth in accordance with religious and universal values.